Validity and intra-session reliability of a low-cost device for assessing isometric mid-thigh pull force - Diego Couto; Rafael Cunha; Victor Lage; Valdinar Rocha-Junior; Wanderson Santos; João B. Ferreira-Junior; James Tufano; Amilton Vieira (Termedia Publishing House, 2023)
Purpose The isometric mid-thigh pull (IMTP) test is a strength test usually requiring expensive equipment like a force platform. Low-cost alternatives could make IMTP testing more accessible. Previous research reported high systematic bias when comparing low-cost devices with more expensive criterion devices (force platforms). This study investigated the concurrent validity and intra-session reliability of a custom-built low-cost IMTP device using a load cell. Methods Overall, 17 recreationally resistance-trained men (25 ± 6 years, 83 ± 14 kg, 178 ± 7 cm, 5 ± 3 years of resistance training experience) first visited the laboratory to be familiarized with testing protocols and returned 2-3 days later for IMTP testing with the low-cost device and a laboratory-grade force platform. Results The overall bias was trivial (-0.8%, 95% CI: -5.7 to 4.3%). The typical error of the estimate was moderate (10.2%, 95% CI: 7.4-16.2%). A strong correlation of 0.91 (95% CI: 0.76-0.97) was found between peak force values from both devices; the low-cost IMTP device accounted for 81.3% of the variation in force platform. The low-cost IMTP also demonstrated acceptable scores for reliability and agreement (ICC = 0.96, 95% CI: 0.89-0.98; typical error = 5.0%, 95% CI: 3.7-7.7%), similar to the criterion (ICC = 0.97, 95% CI: 0.91-0.99; typical error = 4.5%, 95% CI: 3.3-7.1%). Conclusions The low-cost IMTP device using a load cell was valid and reliable for maximal force production in recreationally trained men and provided results comparable with those of a force platform.